Characterization of the N(6)-etheno-bridge method to assess extracellular metabolism of adenine nucleotides: detection of a possible role for purine nucleoside phosphorylase in adenosine metabolism - Jackson, Edwin K. (Purinergic Signal, 2020)
The goal of this study was to determine the validity of using N(6)-etheno-bridged adenine nucleotides to evaluate ecto-nucleotidase activity. We observed that the metabolism of N(6)-etheno-ATP versus ATP was quantitatively similar when incubated with recombinant CD39, ENTPD2, ENTPD3, or ENPP-1, and the quantitative metabolism of N(6)-etheno-AMP versus AMP was similar when incubated with recombinant CD73. This suggests that ecto-nucleotidases process N(6)-etheno-bridged adenine nucleotides similarly to endogenous adenine nucleotides. Four cell types rapidly (t(1/2), 0.21 to 0.66 h) metabolized N(6)-etheno-ATP. Applied N(6)-etheno-ATP was recovered in the medium as N(6)-etheno-ADP, N(6)-etheno-AMP, N(6)-etheno-adenosine, and surprisingly N(6)-etheno-adenine; intracellular N(6)-etheno compounds were undetectable. This suggests minimal cellular uptake, intracellular metabolism, or deamination of these compounds. N(6)-etheno-ATP, N(6)-etheno-ADP, N(6)-etheno-AMP, N(6)-etheno-adenosine, and N(6)-etheno-adenine had little affinity for recombinant A(1), A(2A), or A(2B) receptors, for a subset of P2X receptors ((3)H-α,β-methylene-ATP binding to rat bladder membranes), or for a subset of P2Y receptors ((35)S-ATP-αS binding to rat brain membranes), suggesting minimal pharmacological activity. N(6)-etheno-adenosine was partially converted to N(6)-etheno-adenine in four different cell types; this was blocked by purine nucleoside phosphorylase (PNPase) inhibition. Intravenous N(6)-etheno-ATP was quickly metabolized, with N(6)-etheno-adenine being the main product in naïve rats, but not in rats pretreated with a PNPase inhibitor. PNPase inhibition reduced the urinary excretion of endogenous adenine and attenuated the conversion of exogenous adenosine to adenine in the renal cortex. The N(6)-etheno-bridge method is a valid technique to assess extracellular metabolism of adenine nucleotides by ecto-nucleotidases. Also, rats express an enzyme with PNPase-like activity that metabolizes N(6)-etheno-adenosine to N(6)-etheno-adenine. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11302-020-09699-x) contains supplementary material, which is available to authorized users.